Solubility of two stable iminium salts in 12 polar solvents - Grande, Maria del Carmen (2002)
Despite their biological importance, little is known about the physicochemical properties of iminium salts due to their high reactivity with water. Our group has synthesized several iminium salts that are unusually stable to hydrolysis. In the present work, solubility data are reported as a function of temperature for two of these compounds, namely, 8-acetamide-2,4,4,8-tetramethyl-3-azabicyclo[3.3.1]non-2-ene perchlorate and 8-benzamide-2-phenyl-4,4,8-trimethyl-3-azabicyclo[3.3.1]non-2-ene perchlorate, in 12 different polar solvents. Thermodynamic quantities related to the solution process are calculated.